PENGARUH PELATIHAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PUSAT DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KOTA SURABAYA - Lailatul Fitri Rahmawati; Budiono (PT. Hasba Edukasi Mandiri, 2025)
This study aims to determine the effect of job training on employee performance at the Fire and Rescue Department Headquarters of Surabaya City. The sample size used in this study is 60 samples. The research was conducted by distributing an online questionnaire using Google Forms. This study is a quantitative research with simple linear regression analysis technique. The results show that job training has a significant positive effect on employee performance at the Fire and Rescue Department Headquarters of Surabaya City.